2021
DOI: 10.21203/rs.3.rs-1027370/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deuterium labeling enables non-invasive 3D proton MR imaging of glucose and neurotransmitter metabolism in the human brain

Abstract: Impaired brain glucose metabolism characterizes most severe brain diseases. Recent studies have proposed deuterium (2H)-Magnetic Resonance Spectroscopic Imaging (MRSI) as a reliable, non-invasive, and safe method to quantify the human metabolism of 2H-labeled substrates such as glucose and their downstream metabolism (e.g., aerobic/anaerobic glucose utilization and neurotransmitter synthesis) and address the major drawbacks of positron emission tomography (PET) or carbon (13C)-MRS. Here, for the first time, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In contrast to a direct detection of labeled substrates using DMI ( 2 H-MRS/MRSI), 13 C-MRS, or [ 18 F]FDG-PET the indirect 1 H-based QELT approach allows for simultaneous detection of labeled and unlabeled metabolites to quantify an extended neurochemical profile and requires no additional hardware or radioactive tracers (8)(9)(10). In comparison to recent publications presenting QELT MRSI results in animals (9) and humans (7,8,10) at ultra-high field(≥7T) research systems, our approach provides motion-corrected 3D metabolite maps with high temporal stability (26), which were acquired with high spatial and temporal resolution on widely available clinical 3T MR scanners. Further improvements in spatial and temporal stability can be anticipated considering the wide range of stateof-the-art undersampling or super-resolution techniques in MRSI (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to a direct detection of labeled substrates using DMI ( 2 H-MRS/MRSI), 13 C-MRS, or [ 18 F]FDG-PET the indirect 1 H-based QELT approach allows for simultaneous detection of labeled and unlabeled metabolites to quantify an extended neurochemical profile and requires no additional hardware or radioactive tracers (8)(9)(10). In comparison to recent publications presenting QELT MRSI results in animals (9) and humans (7,8,10) at ultra-high field(≥7T) research systems, our approach provides motion-corrected 3D metabolite maps with high temporal stability (26), which were acquired with high spatial and temporal resolution on widely available clinical 3T MR scanners. Further improvements in spatial and temporal stability can be anticipated considering the wide range of stateof-the-art undersampling or super-resolution techniques in MRSI (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous tracer injection would allow additional blood sampling to estimate isotopic enrichment time courses as an input function to overcome those challenges in future studies (20). A previous study using DMI showed that the increase of deuterium labeled Glx features an approximately linear behavior in the first 60 min (7), therefore, our study used linear fitting as an approximation to estimate the dynamics of Glx, but this approach does not reflect real quantitative turnover rates. Other models, such as exponential fitting has been applied previously, but require longer scan times (e.g., 2-3 hours) and the assessment of a true baseline.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations